Enhancement of Efficacy of Retinoids through Enhancing Retinoid-Induced RAR Activity and Inhibiting Hydroxylation of Retinoic Acid, and Its Clinical Efficacy on Photo-Aging - Seongsu Kang; Hyejin Lee; Seung-Hyun Jun; Sun-Gyoo Park; Nae-Gyu Kang (MDPI AG, 2022)
Retinoids, one of the most robust bioactive materials, have been widely used to improve various dermatological and pathological conditions. The body has an endogenous mechanism that modulates the exogenous retinoid above physiological concentrations, which limits the bioavailability or pharmacological efficacy of retinoids. Considering that most retinoids trigger extensive irritation in users, it is necessary to enhance the pharmacological efficacy of retinoids, thereby achieving a higher efficacy at a lower dosage. Here, we present approaches for enhancing the efficacy of retinol by enhancing retinoid-induced RAR gamma (RAR-γ) activity and inhibiting the hydroxylation of retinoic acid. Using both in vitro and ex vivo experiments, retinoid boosters were demonstrated to enhance pharmacological efficacy. A small pilot study was conducted to investigate the efficacy for improvement of facial wrinkles, whose results revealed that these boosters could enhance the pharmacological efficacy of topical applications of both retinol and retinoic acid for cosmetic use. These results promote not only a higher compliance among retinoids users, but also provide significant insights into the mechanisms underlying the action of retinoids.